Morphology Development in Amorphous Polymer:Fullerene Photovoltaic Blend Films During Solution Casting. (2nd October 2013) - Pearson, Andrew J.; Wang, Tao; Dunbar, Alan D. F.; Yi, Hunan; Watters, Darren C.; Coles, David M.; Staniec, Paul A.; Iraqi, Ahmed; Jones, Richard A. L.; Lidzey, David G.
Abstract : The evolution of film structure is reported during solution casting of PCDTBT:PC70 BM 1:4 wt%, a polymer:fullerene blend system that finds application in an organic photovoltaic device. Using the complimentary techniques of grazing‐incidence wide‐angle X‐ray scattering and spectroscopic ellipsometry, a number of distinct processes that occur during film formation are identified. This includes the growth of fullerene molecules into nanoscale aggregates, the onset of which coincides with the solubility limit of the material in the casting solvent being reached. An apparent delay in Bragg scatter from the PCDTBT‐rich phase of the film suggests that, for the film composition studied here, the aggregation of PC70 BM precedes weak self‐organisation of the conjugated polymer. This behaviour is compared with the drying dynamics of a number of different polymer:fullerene blends that each contain a high weight fraction of fullerene molecules, and a range of comparable solid concentrations are identified beyond which the precipitation of fullerene aggregates from solution occurs. These observations provide an insight into the development of structure in relatively amorphous polymer:fullerene blends for organic photovoltaic applications and potentially assists the future optimisation of this category of materials. Abstract : Thin‐film formation in solution‐cast PCDTBT:PC70 BM 1:4 wt% blend films is characterised using a combination of spectroscopic ellipsometry and grazing‐incidence wide angle X‐ray scattering. A multi‐step process of structure evolution is observed which includes the coalescence of PC70 BM molecules and an apparent delay in weak ordering within the PCDTBT‐rich phases of the film.